The Roles of H2S Gas in Behavior of Carbon Steel Corrosion in Oil and Gas Environment: A Review - Yuli Panca Asmara (Universitas Mercu Buana, 2018)
Hydrogen sulfide (H2S) is the most dangerous element which exists in oil and gas reservoir. H2S acidifies water which causes pitting corrosion to carbon steel pipelines. Corrosion reaction will increase fast when it combines with oxygen and carbon dioxide (CO2). Thus, they can significantly reduce service life of transportation pipelines and processing facilities in oil and gas industries. Understanding corrosion mechanism of H2S is crucial to study since many severe deterioration of carbon steels pipelines found in oil and gas industries facilities. To investigate H2S corrosion accurately, it requires studying physical, electrical and chemical properties of the environment. This paper concentrates, especially, on carbon steel corrosion caused by H2S gas. How this gas reacts with carbon steel in oil and gas reservoir is also discussed. This paper also reviews the developments of corrosion prediction software of H2S corrosion. The corrosion mechanism of H2S combined with CO2 gas is also in focused.